Systematic parameter study of a nonlinear electromagnetic energy harvester with matched magnetic orientation: Numerical simulation and experimental investigation. (15th February 2017) - Deng, Wei; Wang, Ya
Abstract: This paper reports the systematic parameter study of a tristable nonlinear electromagnetic energy harvester for ambient low-frequency vibration. Numerical simulations and experimental investigations are performed on the harvester which consists of a cantilever beam, a tip coil, two tip magnets and two external side magnets. The external side magnets are deployed symmetrically along a concave surface parallel to the trajectory of the cantilever tip with a controllable distance so that the magnetic orientation of the tip magnets are matched with that of the side magnets. Therefore, instead of the ternary position parameters ( d, h, α ), a binary parameters pair ( d 0, d ) is used to characterize the position of the side magnets and the performance of the energy harvester. The magnetic force and magnetic field on the cantilever tip therefore depend on the relative distance in the tip displacement direction between the tip magnets and side magnets, but is independent of the position of the side magnets on the concave surface. The magnetic force (field)-distance relationship is measured experimentally and curve fitted to obtain explicit expressions, in order to characterize the magnetic force (field) when the side magnets are placed at varied positions along the concave surface. Numerical simulation is, then, performed to predict the electromagnetic voltage output and the bandwidth of the energy harvester. The simulation results coincided with the measured data. Significant broadband response is obtained experimentally and the maximum RMS power output is 40.2 mW at 0.45 g of excitation. The proposed structure showcasing the matched magnetic orientation is characterized by the binary parameters pair ( d 0, d ) and the systematic parametric approach could contribute to the design and study of nonlinear broadband energy harvesters. Highlights: This paper reports the systematic parameter study of a tristable nonlinear electromagnetic energy harvester for ambient low-frequency vibration. Numerical simulations and experimental investigations are performed on the harvester which consists of a cantilever beam, a tip coil, two tip magnets and two external side magnets. The external side magnets are deployed symmetrically along a concave surface parallel to the trajectory of the cantilever tip with a controllable distance so that the magnetic orientation of the tip magnets are matched with that of the side magnets. Therefore, instead of the ternary position parameters ( d, h, α ), a binary parameters pair ( d 0, d ) is used to characterize the position of the side magnets and the performance of the energy harvester. The magnetic force and magnetic field on the cantilever tip therefore depend on the relative distance in the tip displacement direction between the tip magnets and side magnets, but is independent of the position of the side magnets on the concave surface. The magnetic force (field)-distance relationship is measured experimentally and curve fitted to obtain explicit expressions, in order to characterize the magnetic force (field) when the side magnets are placed at varied positions along the concave surface. Numerical simulation is, then, performed to predict the electromagnetic voltage output and the bandwidth of the energy harvester. The simulation results coincided with the measured data. Significant broadband response is obtained experimentally and the maximum RMS power output is 40.2 mW at 0.45 g of excitation. The proposed structure showcasing the matched magnetic orientation is characterized by the binary parameters pair ( d 0, d ) and the systematic parametric approach could contribute to the design and study of nonlinear broadband energy harvesters.